THE ROLE OF MODERATION OF ORGANIZATIONAL COMMITMENT ON WORK MOTIVATION TO EMPLOYEE PERFORMANCE - Rofiq, Iwan Setiawan; Ayuningsih, Mawar; Muliati, Lisdewi; Isrok, Isrok (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of work motivation on employee performance moderated by significant or insignificant organizational commitment. The population in this study amounted to 90 respondents and those taken or sampled were still 90 respondents. The sampling technique used is the Probability Sampling technique. The respondents sampled in this study were employees of the Pyhlon Injection Department of PT Pratama Abadi Industri. The method used in this study is quantitative method and data collection is carried out by distributing questionnaires or questionnaires. The results showed that the moderating role of organizational commitment to work motivation on employee performance, with determination of 47.5% and the remaining 52.5% influenced by other factors. The results of this research analysis show that there is a positive and significant influence of motivation on employee performance and there is a positive and significant influence on Work Motivation moderated by Organizational Commitment.